Assessment of Review of Operation of Article 64A of the Sexual Offences Order (Northern Ireland) 2008 : Offence of Purchasing Sexual Services.: Offence of Purchasing Sexual Services. (2019) - Northern Ireland., Department of Justice
No abstract available